PENGARUH CEKAMAN KEKERINGAN TERHADAP PERTUMBUHAN DAN HASIL PADI GOGO LOKAL, KULTIVAR JAMBU - Bambang Supriyanto (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2013)
Dry land is one type marginal land, because of drought caused many negative impacts on plants. Drought will cause a disruption of metabolic processes of plants such as the inhibition of nutrient absortion, inhibition ofcell division and enlargement, decreased enzyme activity and the closure of stomata, so that growth and development of palnts become stunted.This research aims to study the response of soil water stress to growth and yield of Jambu local upland rice. The experiment was conducted in green house, at Faculty of Agriculture, Mulawarman University. The study consisted of one experiments carried out by using a completely randomized design with five replications. Experiments soil water content (W) which consist five levels including field capacity (100%), 90% from field capacities, 80% from field capacity, 70% of field capacity and 60% of field capacity. The results of research that treatment of water stress showed significant different to all data. The best result obtained by treatment of water stress is treatment field capacities (WO).